Disentangling the Social Context of Nonmedical Use of Prescription Stimulants in College Students. Issue 6 (20th May 2020) - Wilens, Timothy E.; Martelon, MaryKate; Yule, Amy; Kaminski, Tamar A.; Burke, Colin; Schepis, Ty S.; McCabe, Sean E.
Abstract : Background and Objectives: The aim of this study was to investigate the social context of nonmedical use of prescription stimulants (NMUPS) among college students who endorsed NMUPS with co‐occurring substance use disorders (SUD) compared with those without co‐occurring SUDs. Methods: Presented here are new analyses based on data previously collected from college students aged 18 to 28 years derived from the Boston metropolitan area who endorsed NMUPS (N = 100) at least once in their lifetime. Differences between those with lifetime history of SUD (N = 46) and without a history of SUD (N = 54) on the Massachusetts General Hospital ADHD Medication Misuse and Diversion Assessment were analyzed using the Student t test, the Pearson χ 2 test, and the Wilcoxon rank‐sum test. Results: College students who endorsed NMUPS with co‐occurring SUD were more likely than those without SUD to have bought or traded stimulants, bought or traded in their car, used at parties with drugs/alcohol, or used intranasally (all P < .05). Intranasal administration was common (38% of all students endorsing NMUPS) and was associated with misuse at a party and simultaneous use with cocaine ( P = .04), marijuana ( P < .001), and alcohol ( P < .001), compared with only oral use. Discussion and Conclusions: Notable characteristics were identified among individuals who engaged in NMUPS in the type, amount, cost, and ascertainment of stimulants. Scientific Significance: The concurrence of SUD and/or intranasal administration appear to represent a more severe phenotype of NMUPS that should be considered in the implementation of future prevention and intervention protocols on college campuses. (Am J Addict 2020;29:476–484)